What distinguishes Ibn Zakur in his grammatical views from the explanations of enthusiasm In his book (The Title of Preciousness in Explaining Enthusiasm) - Yousif Ahmed, Loma; Al-Athari, Bushra Abdul-Razzaq (Al-Adab Journal, 2020)
In our research we examined (the effect of meaning on the Arab rule of Ibn Zakour al-Fassi) in his book "The Title of Precision in Explaining Enthusiasm", We have mentioned evidence from the Court of enthusiasm for Abu Tammam that was distinguished by Ibn Zakour and expressed his opinion about its Arab possibilities. The nature of the research required that it be divided into two requirements. The first requirement is what distinguishes Ibn Zakour from his enthusiasm. The second requirement is Ibn Zakour’s views on his Arab probabilities. The research concluded with the most important results, and it was confirmed by the sources and references.